ภาษาอังกฤษกับการก้าวสู่ประชาคมอาเซียน - ทาวงศ์ษา, กิตติพัฒน์ (วารสารศรีล้านช้างปริทรรศน์; Vol 1 No 2 (2015): วารสารศรีล้านช้างปริทรรศน์ ปีที่ 1 ฉบับที่ 2 (กรกฏาคม - ธันวาคม 2558), 2015)
การก้าวเข้าสู่ประชาคมอาเซียนของคนในภูมิภาคนี้ทำให้ทุกกิจกรรมที่เกี่ยวกับเรื่อง เศรษฐกิจ สังคม การเมือง การปกครอง การศึกษา ศิลปะ วัฒนธรรม ประเพณี การท่องเที่ยว และอื่น ๆ ต้องมีการติดต่อประสานกัน โดยอาศัยภาษาอังกฤษเป็นสื่อกลางในการเชื่อมโยง และหัวใจของการเชื่อมโยงนี้ก็ต้องอยู่ที่ “ครูผู้สอนภาษาอังกฤษ” ในฐานะผู้รับผิดชอบโดยตรง จึงจำเป็นที่ครูผู้สอนภาษาอังกฤษ รวมถึงหน่วยงานต้นสังกัด จะต้องร่วมกันยกระดับและพัฒนาเพื่อให้ประชาคมอาเซียนมีความแข็งแกร่งอย่างสมบูรณ์ โดยเฉพาะอย่างยิ่งการขับเคลื่อนให้พลเมืองทุกคนในกลุ่มประเทศอาเซียนสามารถใช้ภาษาอังกฤษในการสื่อสารได้อย่างมีคุณภาพ The combination of the 10-members of the Association of South East Asian Nations ( ASEAN ) as the region’s economic community, was reflected that all the activities: economic, social, political, government, educational, art, culture, tradition, tourism, etc., were coordinated together and based upon English as the community’s standard language. In addition, the core of coordination was focused upon ‘English teachers’ as ‘persons in charge.’ Therefore, it was the most important for English teachers, including their agencies, to cooperate to enhance, develop and strengthen the community. It looked very special to drive up ASEAN’s citizens to communicate in English fluently.